Análise da diversidade e estrutura genética de variedades de milho pipoca utilizando marcadores microssatélites - Silva, Tereza Aparecida da (2012)
Primers for SSR locos were used in the current research to evaluate genetic diversity and the structure of 31 popcorn genotype from germplasm bank of the State University of Maringá (Maringá, PR, Brazil). 159 pairs of SSR primers, mapped for common maize, were tested. It was found that 26.4% were polymorphs and 30 primers were selected to this study. 127 alleles were identified from these primers between 30 locos evaluated, the number of alleles per loco in the genotypes varied between 2 and 8, with 4.23 alleles/loco. Mean proportion of polymorphic locos in a set of 31 genotypes reached 79.89%, BOZM 260 showed polymorphism to all 30 locos -studied (100%). This genotype can be indicated to cross with plants which show agronomic characteristic wanted to expand the genetic base of popcorn genotype. The primers UMC1549 e UMC1072, showing polymorphism to every genotype, can be considered promising to detect polymorphism in popcorn genotypes. Mean heterozygosity varied between 0.071 and 0.3. The genotype BOZM 260 was the one with the highest proportion of heterozygous plants (0.3) can be considered promising to continued selection of progenies. Evanno et al. (2005) method indicated that the 31 populations are distributed in three groups. The UPGMA method showed that genotype TATU 2 and ARZM 05 083 has higher genetic dissimilarity in relation to the others.